2017
DOI: 10.1039/c7nj03338a
|View full text |Cite
|
Sign up to set email alerts
|

First synthesis of pyrene-functionalized silatranes for mechanistic insights into their potential anti-parasitic and anti-oxidation activities

Abstract: The known silatranes have attached substituents such as hydrogen, organyl, organoxy, aminoalkyl, thioorganyl, acyloxy, halogen, pseudohalogen, and other groups; however, their functionalization with any polycyclic aromatic hydrocarbon substituent is not recognized; this creates a niche in silatrane chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The studies showed that both compounds were capable to act against Giardia lamblia and Trichomonas vaginalis . Moreover, silatrane ( 22 ) had a better effect on T. vaginalis than the standard drugs, for example, Metronidazole IC 50 10 μM; silatrane ( 22 ) IC 50 1.75 μM [ 56 ].…”
Section: Silatranyl Physiologically Active Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies showed that both compounds were capable to act against Giardia lamblia and Trichomonas vaginalis . Moreover, silatrane ( 22 ) had a better effect on T. vaginalis than the standard drugs, for example, Metronidazole IC 50 10 μM; silatrane ( 22 ) IC 50 1.75 μM [ 56 ].…”
Section: Silatranyl Physiologically Active Compoundsmentioning
confidence: 99%
“…The performed investigations [ 56 , 57 , 58 ] demonstrate the importance of the synthesis and application of APS-containing multicomponent antiparasitic agents.…”
Section: Silatranyl Physiologically Active Compoundsmentioning
confidence: 99%
“…Silatranes are tricyclic organosilicon ethers that have various applications such as surface modification, chemosensing, coating, agriculture and various biological activities like antibacterial, antiprotozoal, antiviral, antiparasitic, and antioxidant properties. [20][21][22][23][24][25][26][27][28] Researchers are exploring ways to modify silatranes by combining them with other active molecules to enhance their applications. The acetylenic moiety, a frequently used component in organic chemistry, is being combined with the indole ring to enhance its biological and photophysical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively silatrane, with general formula N-[(CR 1 R 2 ) n O] 3 SiR, can be considered as hypervalent silicon species surrounded by three oxygen atoms and an exocyclic substrate. It includes three heterocyclic caged structures with triethanolamine and transannular bond between nitrogen and silicon atom [4].These pentacoordinated compounds acquires distorted trigonal bipyramidal geometry around silicon atom. The transannular dative bond between nitrogen and silicon is the feature of interest on account of its uniqueness of molecular structure, architectural beauty and peculiar stereoelectronic and chemical properties [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%